Gambaran Tingkat Pengetahuan dan Sikap terhadap Perilaku Swamedikasi Gastritis di Kelurahan Bello Kecamatan Maulafa Kota Kupang - Desi K. N. Dimu; Petrus Romeo; Eryc z. Haba Bunga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Self-medication or self-treatment is an action taken to overcome a disease or symptoms of a disease experienced without going through a diagnosis or supervision from a doctor. Many Indonesian people do self-medication as an effort to treat the complaints/illnesses they experience, usually done to overcome complaints and minor diseases that are often experienced by the community, including gastritis. The purpose of this study is to find out the overview of the level of knowledge and attitudes towards gastritis self-medication behavior in Bello village, this study uses a descriptive method with a quantitative approach. The population in this study is all people with the status of gastritis sufferers in the working area of Bello Village. Samples were taken using a simple random sampling method. This study illustrates that the level of knowledge and attitude of respondents regarding self-directed behavior is still lacking. This can be seen from the number of respondents who think that gastritis is a disease that does not require a doctor's diagnosis, thus encouraging respondents to self-medicate on the basis of advice from family members who also have a history of gastritis.